Molecular Characteristics in MRI-Classified Group 1 Glioblastoma Multiforme - Haskins, William E.; Zablotsky, Bethany L.; Foret, Michael R.; Ihrie, Rebecca A.; Alvarez-Buylla, Arturo; Eisenman, Robert N.; Berger, Mitchel S.; Lin, Chin-Hsing A. (Frontiers in Oncology, 2013)
Glioblastoma multiforme (GBM) is a clinically and pathologically heterogeneous brain tumor. Previous study of MRI-classified GBM has revealed a spatial relationship between Group 1 GBM (GBM1) and the subventricular zone (SVZ). The SVZ is an adult neural stem cell niche and is also suspected to be the origin of a subtype of brain tumor. The intimate contact between GBM1 and the SVZ raises the possibility that tumor cells in GBM1 may be most related to SVZ cells. In support of this notion, we found that neural stem cell and neuroblast markers are highly expressed in GBM1. Additionally, we identified molecular characteristics in this type of GBM that include up-regulation of metabolic enzymes, ribosomal proteins, heat shock proteins, and c-Myc oncoprotein. As GBM1 often recurs at great distances from the initial lesion, the rewiring of metabolism and ribosomal biogenesis may facilitate cancer cells’ growth and survival during tumor migration. Taken together, combined our findings and MRI-based classification of GBM1 would offer better prediction and treatment for this multifocal GBM.